Pengembangan Aplikasi Sistem Pemesanan Cuci Sepatu berbasis Mobile Android pada Garage Shoes Clean - Anggara Priambodo Jhohansyah; Fajar Pradana; Indriati Indriati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Shoe laundromats or shoe washing services in Indonesia were only discussed in 2014. The shoe washing service business began to flourish and was widespread in almost all major cities in Indonesia. This business can be formed, because it cannot be separated from the consumptive nature of the community who are interested in shoes and sneakers. Business people see the enthusiasm of the community for their interest in caring for shoes, making business opportunities for business people to start 2 businesses in this field. Business people see the busy activities carried out by the community but most of them have minimal time to take care of the shoes they have, even though shoes are a mandatory requirement that is used when traveling, going to school, or working. Due to the increasing number of shoe washing service businesses in 2019, players in this field are competing to attract potential customers with new innovations that are continuously being developed. Thus, business people in this field must rack their brains to turn potential customers into consumers of the services they offer. By using an innovation in technology to increase sales. In this study, we will develop an android application for ordering shoe washing to help run this business. The method used in this research is using prototyping. This research begins with the requirements engineering stage which produces 32 functional requirements and 1 non-functional requirement. The implementation phase of this application uses Firebase as a database using the Java programming language. Finally, there is the testing phase with unit testing producing 3 functional values ​​tested valid, validation testing has succeeded in reaching 100% valid according to the expected result, and usability testing resulting in a usability score of a SUS score of 71.5. With this research, it is hoped that it can help in terms of shoe washing services at Garage Shoes Clean.